Does Early Parental Conflict Impact Current Depression Among Older Adults in Rural China? A Chain-Mediated Model Analysis - Deng Y; Ni J; Mao H (Psychology Research and Behavior Management, 2023)
Yuanping Deng,1 Jianchao Ni,2 Huapei Mao3 1Normal College, Jimei University, Xiamen, Fujian Province, People’s Republic of China; 2School of Aerospace Engineering, Xiamen University, Xiamen, Fujian Province, People’s Republic of China; 3School of Business, Wenzhou University, Wenzhou, Zhejiang Province, People’s Republic of ChinaCorrespondence: Huapei Mao, School of Business, Wenzhou University, Wenzhou, Zhejiang Province, 325035, People’s Republic of China, Email huapeimao@163.comPurpose: The study aimed to investigate the relationships between early parental conflict, marital and parent-child relationships, and current depression among rural older adults, and to examine its gender differences.Methods: Using data obtained from the China Health and Retirement Longitudinal Study (CHARLS) conducted in 2018, we selected 2347 adults aged 60 years and older in rural China and used a structural equation model to evaluate the mechanisms behind early parental conflict and current depression among such adults.Results: Early parental conflict impacted current depression among rural older adults, and marital and parent-child relationships played mediating roles in the mechanism. However, there were gender differences in the paths: early parental conflict directly impacted older males’ depression, but not among females; marital relationships acted as a mediator between early parental conflict and current depression among older females, but not among males.Conclusion: Among older adults in rural China, early parental conflict can affect current depression through the indirect path of marital relationships as well as the chain mediating path between marital and parent-child relationships.Keywords: early parental conflict, rural older adults, depression, marital relationships, parent-child relationships